Behaviour of students on social media sites : The Ghanaian Context - Asiedu, Nasir Koranteng; Buadi, Donus Worlanyo; Martin-Yeboah, Ebenezer (International Journal of Knowledge Content Development & Technology, 2023)
Behaviour on social media sites need to be clearly defined so that students would know the clear distinction between the acceptable and unacceptable acts they are supposed to exhibit whenever they get on social media platforms. With the adoption of the survey approach, this study randomly selected 204 students from two renowned universities in Ghana to participate in the study. Using the theory of Technological Determinism, the results of this study indicated that technology has the power to influence human behaviour in a positive and negative manner. The results also brought out the acceptable and unacceptable behaviour that should or should not be exhibited on social media sites by students. The study established the importance of the theory of Technological Determinism to media use. It also gave a vivid description of what is right and not right on social media sites.